2008
DOI: 10.2139/ssrn.1268305
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Tobacco Taxation: Evidence from Geographic Micro-Level Data

Abstract: -This paper uses a recent increase in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 18 publications
4
50
0
Order By: Relevance
“…Another assumption was that tax increases would be fully passed through to the consumer. This is often the case, but subproportionate or supraproportionate tax pass-throughs have also been reported 24 25 20. Similarly, price increases in this study were treated as aggregated values and we did not make a distinction between state and federal taxes.…”
Section: Discussionmentioning
confidence: 89%
“…Another assumption was that tax increases would be fully passed through to the consumer. This is often the case, but subproportionate or supraproportionate tax pass-throughs have also been reported 24 25 20. Similarly, price increases in this study were treated as aggregated values and we did not make a distinction between state and federal taxes.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies in this area relied on the analysis of tobacco industry documents,8 Nielsen Homescan data,10 self-reported price data from tobacco users,11 surveys of tobacco retailers,7 local tax collection data6 or economic modelling and simulation 5 12…”
Section: Discussionmentioning
confidence: 99%
“…In addition, consistent with economic theory, global evidence has also shown that cigarette or alcohol excise taxes are not passed homogeneously to all users [2026,2831]. The pass-through rates may vary widely by brand or type of vendors [25,31], manufacturers’ market power [30], the distance to cheaper resources [20,23,24,26] or the type of excise tax [28,29]. …”
Section: Introductionmentioning
confidence: 97%